Enhance The Awareness of Cash Management and Reporting for Small Medium Enterprise (SME) in Surabaya - Dianne Koan; Rizky Eriandani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Small and Medium Enterprises (SMEs) primarily run their business operation with minimum knowledge of financial management and experience to provide a simple financial report. This condition often brings problems for SMEs in growing their business. In response to these conditions, the team has undertaken social activities called community service (Pengabdian Masyarakat) through training and assistance for SMEs in Rungkut, Surabaya. This assistance aims to enhance the understanding of SMEs regarding the concept of business entity and financial management. After finishing activities of community services, SMEs are expected to have a better understanding of financial management and be able to prepare financial reports for their business.